Analyzing spatio-temporal changes and trade-offs/synergies among ecosystem services in the Yellow River Basin, China. (May 2022) - Geng, Wenliang; Li, Yanyan; Zhang, Pengyan; Yang, Dan; Jing, Wenlong; Rong, Tianqi
Highlights: We have assessed the long-term ecosystem services (ESs) of the Yellow River Basin. Future change trends in ESs will either increase or decrease in different regions. The relationship among different ESs in the region are mainly synergies. Multiple factors jointly affect the changing trend and related relationship of ESs. Abstract: Global changes have significant impacts on changes in ecosystem services (ESs) and their interrelationships. The Yellow River Basin (YRB) is an important ecological barrier in China, and it is important for ecological decision-making and management in the basin by quantitatively assessing the trends and drivers of ESs and analyzing the trade-offs and synergies among them. In this study, the food production model, InVEST model, and RUSLE model were used to quantitatively assess three ESs (food production, water yield, and soil conservation) in the YRB from 2000 to 2018. The spatio-temporal trends and future trends were quantified using Theil-Sen Median trend analysis and Hurst exponent. Correlation analysis was used to determine the main influencing factors of the spatio-temporal changes of ESs and analyze the trade-offs and synergies among ESs. The research results show that during 2000–2018, in terms of spatial distribution, food production in the YRB gradually decreases from east to west, water yield gradually decreases from south to north, and the dominant areas of soil conservation are mainly distributed in the plateau areas in the upper and middle reaches of the basin; in terms of temporal changes, food production shows a continuous increase, while water yield and soil conservation generally show an increasing trend in fluctuation. Excluding areas with no significant change and random change, food production will mainly show improvement in the future, and water yield and soil conservation will show some degree of decline in the future. Food production is mainly influenced by the type of land use, water yield is mainly influenced by precipitation, and soil conservation is influenced by a combination of slope and land use type. ESs in the YRB were generally dominated by synergy but locally dominated by trade-offs. Our results will provide reference for policymakers in ecological construction, and analyze trade-offs and synergies of regional ESs in a holistic and local context based on the assessment results and change trends of ESs, thus providing a basis for formulating scientific and reasonable ecological protection policies, and will promote the high-quality development of the YRB.